Short-term effects of prolonged strenuous endurance exercise on the level of haematocrit in amateur cyclists - Neumayr, G.; Pfister, R.; Mitterbauer, G.; Gaenzer, H.; Joannidis, M.; Eibl, G.; Hoertnagl, H. (International Journal of Sports Medicine, 2002)
Knowledge is sparse about the extent of potential dehydration due to prolonged strenuous cycling and its haematological acute effects on the haematocrit (Hct) in study populations credibly not taking any kind of doping. With increasing training load levels of Hct and haemoglobin (Hb) decrease in both amateurs and professionals as a long-term consequence due to expanded plasma volume (PV). On a short-term basis, however, counteracting dehydration potentially brought about by endurance exercise may cause a rise in Hct bringing competitive cyclists into conflict with the current condition regulations and Hct cut-off of 50 % set by the International Cycling Union (UCI) in its fight against erythropoietin (rhEPO) doping. On the other hand adequate and sufficient fluid substitution being substantial for a successful endurance performance should prevent any pronounced Hct rises. To study the haematological acute effects of prolonged strenuous cycling we measured Hct, Hb, red blood cell (RBC) count and plasma protein in a reliably 'clean' population of 38 well-trained male amateur cyclists before, immediately after and one day after an extraordinary ultramarathon. The pre-race levels of Hct, Hb and RBC count were placed in the lower range of normal distribution and well below the Hct cut-off limit of the UCI. Immediately post-exercise the mean levels of Hct, Hb, RBC count and protein remained unchanged. One day after race, however, all four parameters significantly dropped by 3 %, 6.7 %, 6.5 %, 9.9 % respectively (p < 0.001), indicating marked post-exercise PV expansion. The calculated percentage increase in PV was 11.9 %. No evidence for coexisting exercise-induced haemolysis was found. Our study shows that in "clean, rhEPO-free" amateur cyclists who involve in strenuous marathon cycling the haematological short-term effects of extraordinary marathon cycling consist in considerable PV expansion making Hct values fall on the following day. The findings - gained from amateurs though - suggest that despite all its disadvantages the UCI Hct cut-off represents an appropriate means to discourage from excessive rhEPO doping at least as long as the available direct methods for detecting this kind of misuse are not yet applied by the international sports federations.